Mapping obesity and diabetes’ representation on Twitter: the case of Italy - Lenzi, Francesca Romana; Iazzetta, Ferdinando (Frontiers in Sociology, 2023)
One of the main functions of public health is to monitor the health of the population to identify health problems and priorities. Social media are increasingly used to promote it. The study aims at investigating the field of Diabetes and Obesity and the related Tweets in the health and disease framework. The database extracted with academic API (Application Programming Interface) enabled the study to be managed with content analysis and sentiment analysis techniques (Gabarron 2019). These two analysis techniques are some tools of choice for the goals that have been set. The content analysis facilitates the representation of a concept and a connection between two or more concepts such as diabetes and obesity on a purely textual social platform like Twitter (Amaturo, Punziano 2013). The sentiment analysis enables to explore the emotional side connected to the data collected relating to the representation of those concepts (Gilbert 2016). The results show a variety of representations connected to the two concepts and their correlations. From them it was possible to produce some clusters of elementary contexts and to structure narrative and representative dimensions on the concepts investigated with regard to the social platform (Lancia 2004). The use of sentiment analysis and content analysis and the output of cluster to represent complex contexts as diabetes and obesity for a social media community could increase the knowledge of how virtual platforms impact fragile categories, facilitating concrete relapses on public health strategies.